PENGGUNAAN MEDIA PEMBELAJARAN AUDIO-VISUAL DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Rusiadi Rusiadi (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2018)
Media is an element that cannot be separated from other elements that function as a way to deliver learning materials to arrive at the goal. The use of media in the learning process has the benefit of clarifying the subject matter presented, helping students understand and adding variety in teaching. Therefore, the limitations of time and material do not reach the details, but this can be overcome by the use of relevant media. Audio-visual learning media has functions and benefits as a means or aids in teaching and learning activities, namely in the form of facilities that can provide an overview of the audio-visual experience to students in order to encourage learning motivation, clarify and simplify complex and abstract concepts into simple ones. This function is the basic function of audio-visual learning media. Thus, it can be said that the audio-visual learning media serves to increase students' absorption of the learning material presented by the teacher.